Overcoming power distance and deferential speech syndrome in the operating room - Dunn, Jennifer (Operating Room Nurses Association of Canada Journal, 2025)
Power distance, mitigated speech, and top-down decision paradigms in perioperative care undermine collaboration and compromise patient safety (Kenawy & Schwartz, 2018). These challenges disproportionately affect perioperative nurses, fostering deferential speech syndrome (DSS)—a habitual use of softened language shaped by entrenched power dynamics. Deferential speech syndrome reduces assertiveness, weakens safety-sensitive communication, and amplifies risks associated with hierarchical decision-making, moral injury, and fatigue-induced errors (Applebaum et al., 2020). Understanding these dynamics necessitates exploring interventions to counteract DSS and its detrimental effects, while addressing the challenges that may arise in their implementation. To address the pressing challenges posed by DSS, evidence from healthcare and analogous high-stakes industries highlights effective strategies for intervention. Actionable solutions include fostering psychological safety to empower all team members (Grailey et al., 2021) and adopting crew resource management (CRM) principles to disrupt power imbalances (Gross et al., 2019). Short-term interventions, such as structured communication tools (e.g., SBAR protocols and closed-loop communication), pre-operative planning sessions, leadership huddles, and bias-awareness training can provide immediate improvements in perioperative collaboration and patient safety. Additional measures, including anonymous feedback systems and post-operative debriefings, further reinforce an environment where critical concerns can be raised without fear of retribution. However, successfully implementing these interventions requires overcoming barriers, such as entrenched hierarchical norms, resistance to change, and resource constraints, all of which will be critically examined. These strategies lay the groundwork for long-term reforms, including leadership development programs, decision-support technologies, and equitable operational policies (Tørring et al., 2019). By integrating these targeted interventions, healthcare institutions can mitigate DSS, reduce hierarchical barriers, and enhance safety-sensitive communication, fostering a culture of inclusivity and collaboration that ultimately improves patient outcomes and team well-being. While these strategies represent critical first steps, a broader systemic approach is crucial to sustain long-term improvements in perioperative care. The urgency of addressing DSS extends beyond operational efficiency; it is a moral imperative essential to creating equitable, resilient perioperative environments that uphold ethical standards and optimize care delivery. By dismantling hierarchical barriers, prioritizing collaboration, and fostering inclusivity, healthcare systems can establish a model for high-performing surgical teams that enhance both patient outcomes and team well-being.